A Mini Review: The Potential Biomarkers for Non-invasive Diagnosis of Pulpal Inflammation - Kaur, Brahmleen; Kobayashi, Yoshifumi; Cugini, Carla; Shimizu, Emi (Frontiers in Dental Medicine, 2021)
For assessing the adequacy of vital pulp therapy for an inflamed pulp the use of non-invasive diagnostic tools is necessary to avoid further damage to the teeth. Detection of biomarkers that are indicative of the inflammatory status in pulp can be a promising tool for this purpose. These biomarkers need to be reliably correlated with pulpal inflammation and to be easily detected without pulp exposure. This mini-review article aims to review biomarkers that are present in gingival crevicular fluid (GCF) in inflamed pulp conditions. Several studies have reported the availability of various biomarkers including cytokines, proteases, elastase, neuropeptides, and growth factors. Non-invasive pulpal diagnostic methods will be useful as well to determine reversibility, irreversibility, or necrosis of inflamed pulp. These types of molecular diagnoses via analyzing the proteome have revolutionized the medical field, and are one of the most promising empirical methodologies that a clinician can utilize for the proactive identification of pulpal disease.